Socio-Cultural and Ethno-botanical knowledge of Aidy: An Anthropological Study of Mimi VDC OF Humla - Sapkota, Prakash Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2006)
DOI: 10.3126/dsaj.v1i0.278 Dhaulagiri Vol.1 (2005) pp.97-109